Refugee Settlement and Decision-Making Venue: Does Public Concern Instigate Preferences for Local Referendums? Experiences from Norwegian Cities. (18th August 2021) - Steen, Anton
Abstract: Refugee settlement in local communities is often controversial and raises questions of legitimate regulation of access and sustainable integration. This study takes the citizens' perspective and asks who should determine refugee settlement—the people in a local referendum, political representatives in the local council, or elites in central government—as well as enquiring how immigration scepticism affects preferences for the decision-making venue. The issue speaks to the wealth of literature focusing on 'the local dimension' of immigration. The data are from opinion surveys in four Norwegian cities that have experienced extensive refugee settlement during the past few decades. Contrary to expectations, it appears that despite widespread concern about the consequences of newcomers, most trust the decisions made by their local representatives in the city council and prefer the state to enforce refugee settlement at the local level. As expected, those with negative images of refugees, those with a low level of education, and those with rightist party sympathies tend to support a referendum. More surprisingly, a high level of concern for 'the others' substantially reduces the general positive effects of social background and political orientation: the worried among the well-educated and left-wingers join forces with the right-wingers and politically alienated in supporting referendums as a channel for influencing the settlement issue. This article suggests that the refugee settlement issue is too controversial to be solved by direct democracy and is also a potential channel for those fearing 'the others' across social strata.